The Impact of Inventory-to-Asset Ratio on Firm Value: Evidence from Emerging Markets - Burkhanov Nazarkhon Gulomjon Ugli; Budi Supriatono Purnomo; Irsyad Fauzan Prasetia (Journal of Social Science and Humanities, 2026)
This study examines the effect of the Inventory-to-Asset Ratio (IAR) on firm value among Consumer Cyclicals companies listed in Indonesia and Malaysia, two key emerging markets in Southeast Asia. Using secondary data from the Refinitiv Eikon database, the research applies a pooled cross-sectional quantitative approach to 298 firm-year observations. Ordinary Least Squares (OLS) regression is employed, with Price Close (USD) as a proxy for firm value. The findings reveal that IAR has a negative but statistically insignificant effect on firm value (β = −0.157, t = −1.630, p = 0.104; R² = 0.009). This indicates that capital markets in these countries do not consistently incorporate inventory efficiency into equity valuation. The study contributes to the literature by providing one of the first empirical tests of the IAR–firm value relationship in the ASEAN Consumer Cyclicals sector, challenging the universality of Signalling Theory and extending insights within the Resource-Based View framework. Practically, managers should still maintain efficient inventory practices for long-term performance, while policymakers are encouraged to enhance disclosure standards. Limitations include the single-variable model, proxy choice, and cross-sectional design, suggesting future panel-based research with broader controls.